A conceptual framework of living labs for people: Fostering innovations for low emissions food systems and social equity - Rietveld, Anne M.; Haberman, Birgit; Nehring, Ryan; Zhang, Wei; Falk, Thomas; Kibet, Walter (Bioversity International and the International Center for Tropical Agriculture, 2023)
This paper provides the conceptual basis for what we call Living Labs for People (LL4P). We define LL4P as an inclusive and diverse space for people to design, test, demonstrate and advance their socio-technical innovations and associated modes of governance within a facilitated organizational structure. Our specific aim with LL4P is to facilitate locally developed innovations for low-emission food systems that address social equity in four target countries: China, Colombia, Kenya and Vietnam. This conceptual paper outlines a framework to guide activities in each of those four countries. The LL4P draws on the living lab literature but tailors existing approaches for food systems in developing countries. Four country teams, made up of CGIAR researchers and national partners, adapt LL4P to the specific socio-ecological and cultural context and in line with each country’s mitigation policy such as the Nationally Determined Contribution (NDC). Therefore, while this conceptual paper provides a rationale, framework and a set of guidelines, it will also incorporate distinct approaches from each of the four target countries in line the following principles: 1) gender and social inclusion; 2) the co-production of knowledge; 3) territorial governance and; 4) co-benefits contributing to the Sustainable Development Goals. The practical experience from applying this framework in the four case studies will generate learnings about alternative pathways for other Living Labs focused on low-emission food system development and social equity.